IMPLEMENTASI PERATURAN GUBERNUR ACEH NOMOR 5 TAHUN 2018 DI KABUPATEN ACEH TIMUR - Fajar Adi Putra (Suloh:Jurnal Fakultas Hukum Universitas Malikussaleh, 2021)
Aceh is a province in Indonesia that applies Islamic law in law enforcement, not infrequently in law enforcement in East Aceh District by prosecutors experiencing obstacles in applying Aceh Governor Regulation No. 5 of 2018 for the perpetrators of Jarimah, so that the implementation up to now the Prosecutor is guided by the Aceh Qanun Number 7 of 2013 concerning Jinayat Procedural Law. This study aims to find out how the implementation of the Aceh Governor's Regulation No. 5 of 2018 by the Prosecutors in East Aceh District and why the implementation of the Aceh Governor's Regulation is experiencing obstacles. This study uses an empirical juridical approach to the research location in Lapi Class II B Idi, as well as using secondary data and primary data, then collecting data from literature, interviews and observations, and from the results of these data the data are arranged in a descriptive analysis. The conclusion of this study is that Aceh's Governor Regulation Number 5 Year 2018 cannot be implemented in Idi Class II B Prison, so that in carrying out the Prosecutor's whip uqubat based on Article 262 Aceh Qanun Number 7 of 2013, this is due to obstacles encountered by the Prosecutor in implement the Governor Regulation Number 5 of 2018, including the absence of facilities and infrastructure in Class II B Idi prison, the absence of Technical Instructions and Implementing Guidelines related to the implementation of Governor Regulation Number 5 of 2018 from the Aceh High Prosecutor Office and Class II B Idi Prison, the budget which is limited from the local government, will cause a commotion between prisoners, and the community does not know the whip, given the spirit of the whip is to give the effect of shame on the perpetrators and provide lessons for the community.